2014
DOI: 10.1097/01.jaa.0000453237.17130.6b
|View full text |Cite
|
Sign up to set email alerts
|

Comparing two methods of thoracoscopic sympathectomy for palmar hyperhidrosis

Abstract: No difference was found between the multiple- and single-port methods. Both are effective, safe minimally invasive procedures that permanently improve quality of life in patients with palmar hyperhidrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The same procedure was adopted in both the patients. Some studies have reported bilateral thoracoscopic cervical sympathectomy 5,8 , as a treatment for Palmar and axillary hyperhydrosis, however, our findings show that unilateral thoracoscopic sympathectomy gives similar results in improvement of symptoms, and quality of life of the patient. The decrease in the heart rate revealed that, overall sympathetic hyperactivity had been controlled.…”
Section: Methodsmentioning
confidence: 41%
See 1 more Smart Citation
“…The same procedure was adopted in both the patients. Some studies have reported bilateral thoracoscopic cervical sympathectomy 5,8 , as a treatment for Palmar and axillary hyperhydrosis, however, our findings show that unilateral thoracoscopic sympathectomy gives similar results in improvement of symptoms, and quality of life of the patient. The decrease in the heart rate revealed that, overall sympathetic hyperactivity had been controlled.…”
Section: Methodsmentioning
confidence: 41%
“…No difference was found between the multiple-and single-port methods. Both are effective, safe, minimally invasive procedures, that permanently improve the quality of life in patients with Palmar generalized hyperhidrosis 8.…”
mentioning
confidence: 99%